2010
DOI: 10.1126/science.1178085
|View full text |Cite
|
Sign up to set email alerts
|

Water Freezes Differently on Positively and Negatively Charged Surfaces of Pyroelectric Materials

Abstract: Although ice melts and water freezes under equilibrium conditions at 0 degrees C, water can be supercooled under homogeneous conditions in a clean environment down to -40 degrees C without freezing. The influence of the electric field on the freezing temperature of supercooled water (electrofreezing) is of topical importance in the living and inanimate worlds. We report that positively charged surfaces of pyroelectric LiTaO3 crystals and SrTiO3 thin films promote ice nucleation, whereas the same surfaces when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
216
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(228 citation statements)
references
References 23 publications
9
216
1
Order By: Relevance
“…T w can be determined from the ∆T estimated earlier. The water droplet static contact angle, θ, the nominal size of surface roughness, R s , and the critical ice nucleus radius (that is, the minimum size an incipient ice crystal needs to reach to maintain a stable freezing process), r c 19 , are the principal parameters determining the factor f in equation (3). The roughness parameter can be better appreciated by seeing the scanning electron microscope image in Supplementary Figure S4.…”
Section: Nucleation Mechanismsmentioning
confidence: 99%
“…T w can be determined from the ∆T estimated earlier. The water droplet static contact angle, θ, the nominal size of surface roughness, R s , and the critical ice nucleus radius (that is, the minimum size an incipient ice crystal needs to reach to maintain a stable freezing process), r c 19 , are the principal parameters determining the factor f in equation (3). The roughness parameter can be better appreciated by seeing the scanning electron microscope image in Supplementary Figure S4.…”
Section: Nucleation Mechanismsmentioning
confidence: 99%
“…Experimentally, electrically-induced freezing, or an enhanced tendency to nucleate ice, were claimed to be observed at the electrostatically-charged surfaces of conductors 12,15,16,35 , polar amino acid crystals 14 , and pyroelectric crystals 21 . Water freezing experiments carried on charged surfaces suggested that electric fields much smaller than the predictions of simulations influence the nucleation of ice; nevertheless, careful freezing experiments carried under external electric fields [11][12][13]20 did not observe any effects of the electric field on the nucleation of ice.…”
Section: (V)mentioning
confidence: 99%
“…Electric fields are often encountered in water near the surface of particles, molecules, and ions; they might play an important role in the heterogeneous nucleation of ice by impurity particles 9,14,21,27 .…”
Section: (V)mentioning
confidence: 99%
See 1 more Smart Citation
“…Unique applications, such as developing a transiently charged crystal assembly due to the pyroelectric nature of ZnO (such as those in Fig. 1C) can now be envisioned (12,13).…”
mentioning
confidence: 99%